Algeria’s GIA: The First Major Armed Group to Fully Subordinate Jihadism to Salafism - Thurston, Alexander (Islamic law and society, 2017)
In the mid-1990s, the world’s most successful jihadi group – the group that came closest to overthrowing an Arab regime – was Algeria’s Groupe islamique armé (Armed Islamic Group, GIA). Here I argue that the GIA was the first major armed group to prioritize adherence to Salafi theology over the jihadi strategic objective of building a “big tent.” The GIA used the vocabulary of Salafism to justify killing rivals and would-be allies and eventually turned against the Algerian population itself. In part one, I re-read GIA sources, particularly the group’s London-based newsletter Al-Anṣār, to show how the GIA sidelined potential allies in the name of purity. In parts two and three, I examine the effects of this approach. Through analysis of counter-texts by the GIA’s ideological and theological rivals, I demonstrate how their rejection of the GIA sharpened disagreements about what it meant to be a Salafi-jihadi.